An Exploration of the Use of Educational Robotics in Preschool Education - Veronica Mihaela Rus; Beatrice Almășan (Educaţia 21)
Digital technologies are increasingly present in the daily lives of adults and children, which increases the need to better understand this digital world. Given today's society, the premises of the key competencies that early childhood education must provide future students based on the Curriculum for Early Childhood Education and supported by constructivist theory (of Vygotsky's zone of proximal development), this study aims to investigate the development of computational thinking for the child in preschool education. Using as a method for the case study, the observation of children's behavior during nine weeks in which we carried out specific activities, we tested three hypotheses regarding the development of computational thinking, using both connected and non-connected tools, the levels of communication and collaboration between the participating children. The results show that the use of educational robots in different stages of teaching, learning and evaluation helps in the development process of children by understanding the cause-effect relationship, acquiring spatial and temporal orientation skills, developing communication skills and supporting socio-emotional interactions with children of the same age. Decomposition, abstraction, pattern recognition and algorithms were the four components of computational thinking analyzed and all obtained a score above the mean of the Likert scale used. Future research is needed to study the more in-depth effects of STEAM activities on children's cognitive acquisitions and social-emotional skills.